Hubungan Kemampuan Berpikir Logis dengan Kemampuan Menulis Karangan Aargumentasi Siswa Kelas X SMA Negeri 1 Rao Kabupaten Pasaman - Putri, Gusnita Roza; R., Syahrul; Gani, Erizal (Universitas Negeri Padang, 2012)
The purpose of this study is to describe and analyze, (1) logical thinking ability of students, (2) argument essay writing skills of students, and (3) the relationship of logical thinking ability with the ability to write essays arguing graders X SMA Negeri 1 Rao Pasaman district. This research using quantitative approach with the korelasional method. This is a sample research students of class X SMA Negeri 1 Rao Pasaman listed in the 2011/2012 school year with the number of 34 people. This research Data obtained through objective tests for logical thinking ability and performance tests for the ability to write essays arguing. Research findings the first, that logical thinking ability of students is sufficient qualification with an average rating of 63,53. Second, the ability to write essays arguing students is qualifying more than enough with the average value of 72.79. Third, there is a relationship between logical thinking ability with the ability to write essays arguing students district with thitung obtained is 3.02 and 1,697 ttabel means thitung is greater than ttabel. Thus H1 is accepted and H0 is rejected. Based on those results can be noted that the ability to think logically-related argument essay writing skills of students. The better the students ability in logical thinking, then the better the students ability in writing as well as a bouquet of argumentation.